2023
DOI: 10.1111/psyp.14305
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of response time outliers: Outlier related potentials

Abstract: In response time (RT) research, RTs which largely deviate from the RT distribution are considered "outliers". Outliers are typically excluded from RT analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The relevance of data pre-processing for the inspection of effect courses was further highlighted by a total lack of the response repetition effect, if incorrect trials were not excluded from analysis (see Supplementary Material D ). Accordingly, following a similar logic as it is usual assumed in traditional analysis strategies of RTs/ERs 48 50 , the exclusion of trials which likely do not represent the cognitive phenomena of interest seems to be crucial before conducting an effect course analysis. Following this line of reasoning, the interpretation of the temporal position of the obtained clusters within the experimental session should not be considered in terms of the presented trial in the experiment itself, but in terms of a relative position within the trials of the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of data pre-processing for the inspection of effect courses was further highlighted by a total lack of the response repetition effect, if incorrect trials were not excluded from analysis (see Supplementary Material D ). Accordingly, following a similar logic as it is usual assumed in traditional analysis strategies of RTs/ERs 48 50 , the exclusion of trials which likely do not represent the cognitive phenomena of interest seems to be crucial before conducting an effect course analysis. Following this line of reasoning, the interpretation of the temporal position of the obtained clusters within the experimental session should not be considered in terms of the presented trial in the experiment itself, but in terms of a relative position within the trials of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…We included the data of all 1015 available participants in the dataset. For the analysis of RT data, we excluded trials with an incorrect response as well as trials with a RT exceeding +− 2 SD of the individuals mean RT 48 , 59 . For the analysis of ERs, only trials with an RT outlier were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…relative to cue onset. Trials with an RT outlier were identified as trials with an RT exceeding +-2SD of the respective individuals mean RT and excluded from all subsequent analyses (Berger & Kiefer, 2021, 2023. Segments overlapping with a previous segment were excluded as well.…”
Section: Eeg Recording and Preprocessingmentioning
confidence: 99%